The Verbal Image of Volyn Polissia in the Novel «Nets for Polissia» by Vasyl Hei (Linguostylistic Studies, 2018)
The article elucidates the formation of a lexical-semantic system in the novel by Vasyl Hei, entitled “Nets for Polissya”, through which a verbal image of Volyn Polissya is created. It was found out that the peculiarity of its formation is the frequent use of various lexical-semantic fields, microfields and groups that: 1) describe the uniqueness of the areas; 2) nominate the water reservoirs; 3) depict the forest as a holistic biological system. The field analysis technique allows single out the nuclear, near-nuclear and peripheral zones of its modeling. The core of this system is presumably the nominations of the Volyn water areas (its lakes, rivers, swamps, which are mostly proper names) and forests (trees, flowers). In the text, there is not only an explicit hierarchy of typological elements of the lexical-semantic field of the concept of nature, but there also exists an objective interaction and dependency between them. An important element of the individual style of Vasyl Hei is a harmonious combination of the customary colloquial common names, characteristic of Volyn Polissya and occasional tokens. For example, the lexical-semantic field of water is verbalized through the following supporting diminutive tokens: lake (ozertse), well (krynychka), river (richechka), swamp (bolitse), etc. It is also important to mention that the nominations of almost all fixed semantic fields and groups are formed on the basis of creating numerous figurative contexts, the most expressive among which, in our opinion, is metaphorical.
Keywords: dominant lexemes; lexical microgroups; landscape description; figurative nomination